The Role of Place Cues in Voluntary Stream Segregation for Cochlear Implant Users. (January 2018) - Paredes-Gallardo, Andreu; Madsen, Sara M. K.; Dau, Torsten; Marozeau, Jeremy
Sequential stream segregation by cochlear implant (CI) listeners was investigated using a temporal delay detection task composed of a sequence of regularly presented bursts of pulses on a single electrode (B) interleaved with an irregular sequence (A) presented on a different electrode. In half of the trials, a delay was added to the last burst of the regular B sequence, and the listeners were asked to detect this delay. As a jitter was added to the period between consecutive A bursts, time judgments between the A and B sequences provided an unreliable cue to perform the task. Thus, the segregation of the A and B sequences should improve performance. In Experiment 1, the electrode separation and the sequence duration were varied to clarify whether place cues help CI listeners to voluntarily segregate sounds and whether a two-stream percept needs time to build up. Results suggested that place cues can facilitate the segregation of sequential sounds if enough time is provided to build up a two-stream percept. In Experiment 2, the duration of the sequence was fixed, and only the electrode separation was varied to estimate the fission boundary. Most listeners were able to segregate the sounds for separations of three or more electrodes, and some listeners could segregate sounds coming from adjacent electrodes.